Global, regional, national prevalence, mortality, and disability-adjusted life-years of cutaneous squamous cell carcinoma and trend analysis from 1990 to 2021 and prediction to 2045 - Liu, Chengling; Liu, Xingchen; Cao, Pengjuan; Li, Xin; Xin, Haiming; Zhu, Sailin (Frontiers in Oncology, 2025)
BackgroundA serious worldwide health concern is cutaneous squamous cell carcinoma (cSCC). For the purpose of creating focused strategies, it is essential to comprehend geographical variations in cSCC prevalence and trends.MethodsThis study utilized data from the 2021 Global Burden of Diseases (GBD) survey to analyze cSCC across 204 countries and territories. We assessed the age-standardized prevalence rate (ASPR), mortality rate (ASMR), disability-adjusted life years (ASDR), and estimated annual percentage changes (EAPCs), with trends stratified by region, country, age, sex, and Sociodemographic Index (SDI). To evaluate disparities in cSCC burden, we combined the SDI with the inequality slope and concentration indices for an international health inequality analysis. Decomposition analysis assessed the effects of population growth, aging, and epidemiological trends on disease burden, while frontier analysis linked cSCC outcomes with socio-demographic development. A Bayesian Age-Period-Cohort (BAPC) model projected future prevalence, mortality, and DALYs, identifying key drivers of cSCC burden.ResultsIn 2021, there were 2,275,834 cases of cSCC globally, reflecting a 345% increase since 1990. During this period, the ASPR rose from 14.69 to 26.85 per 100,000, while the ASMR increased slightly from 0.67 to 0.69 per 100,000. Disability-adjusted life years (DALYs) rose from 544,973 to 1,210,874. Among socio-demographic regions, the high SDI region had the highest ASPR, while the middle SDI region exhibited the highest ASMR and ASDR. Decomposition analysis identified population growth and demographic aging as key drivers of the rising ASMR. Countries like Georgia showed significant disparities in frontier analysis, indicating potential for better cSCC management. Health inequality analysis confirmed that the burden was concentrated in nations with higher SDI. By 2045, the global ASPR is projected to reach 64.66, with the ASMR and ASDR expected to decrease to 1.02 and 20.63 per 100,000, respectively.ConclusionOver the last three decades, the global burden of cSCC has increased significantly. While mortality rates and DALYs are expected to decline over the next twenty years, the prevalence of cSCC is projected to remain high. This highlights the urgent need to reevaluate preventive efforts aimed at reducing morbidity, particularly in areas with substantial populations over the age of 95.